Pengaruh Financial Knowledge dan Financial Technology Terhadap Perilaku Keuangan (Studi Pada Siswa-Siswi SMA N 1 Gringsing Kabupaten Batang) - Dyah Ayu Wulandari; Siti Aminah; Hikmah Hikmah; Janti Soegiastuti (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine and analyze the influence of financial knowledge and financial technology on the financial behavior of students at SMA N 1 Gringsing, Batang Regency. The background of this research is based on the increasing use of digital financial services among adolescents, which has not been fully accompanied by responsible and proper financial management behavior. In addition, there is still a gap between the level of financial literacy and the level of financial inclusion among young people, which potentially affects the quality of their financial management. This research employed a quantitative approach using a survey method by distributing questionnaires to 88 respondents. The sampling technique used was proportionate stratified random sampling. The collected data were then analyzed using multiple linear regression analysis. The results indicate that financial knowledge has a positive and significant effect on financial behavior. Furthermore, financial technology also has a positive and significant effect on financial behavior. These findings suggest that the higher the level of financial understanding and the more optimal the utilization of financial technology, the better the students’ financial behavior will be. This study implies that enhancing financial literacy education and promoting the wise use of digital technology should be implemented within the school environment.